Strictly Locating Sets in a Graph - Stephanie A. Omega; Ina Marie P. Kintanar (International Journal of Mathematics And its Applications, 2018)
Let G be a connected graph. A subset S of V(G) is a locating set in G if for all u,vV(G)S, N_G(u)S eq N_G(v)S. A subset S of V(G) is a strictly locating set in G if S is a locating set in G and N_G(w)S eq S wV(G)S. The minimum cardinality of a strictly locating set in G, denoted by sln(G), is called the strictly locating number of G. In this paper, the concept of strictly locating set in a graph is investigated. Moreover, the strictly locating sets in the join and corona of graphs are characterized and the strictly locating numbers of these graphs are determined.